LEGAL ANALYSIS OF THE DETERMINATION OF THE SUSPECT BY THE KPK AFTER IT WAS DECLARED LEGITIMATE IN A PRE-TRIAL DECISION IN INDONESIA - Roland Sahat Uli Banjarnahor; Ismaidar (Universitas Efarina, 2024)
Pretrial is something institution For test validity a case process criminal before case the reached the stage inspection principal case in court , related with determination of suspect status follow criminal often there are pros and cons from various party , determination of suspect status is authority from investigator , as has been outlined in the Criminal Procedure Code. Move on from determination of suspect status by regulated investigators through the Criminal Procedure Code, then task The determination of suspect status is also up to the investigator Commission Eradication Corruption (KPK) which is firm has arranged in Corruption Eradication Commission Law , throughout No arranged in the Corruption Eradication Committee Law and Law Eradication Act Criminal Corruption , then return to existing rules​ in the Criminal Procedure Code. Article 1 point 14 of the Criminal Procedure Code formulates that “ Suspect is someone who because his actions or the situation , based on proof At first , it's appropriate allegedly as perpetrator follow criminal .